Tomorrow's markets : global trends and their implications for business (Washington : World Resources Institute, 2002)
Business
Keywords: Markets; Society; Population; Wealth; Nutrition; Health; Education; Innovation; Ecosystems; Agriculture; Water; Urbanization; Mobility; Communications; Labor; Democracy; Accountability; Privatization